Corrosion Mitigation with Chemical Injection in Welded Carbon Steel Pipe for Offshore Water Treatment Plant - Henry Ekene Mgbemere; Johnson Olumuyiwa Agunsoye; Kenechi Ijeoma Ojemeni; Obianuju Vivian Izuegbu (ABUAD Journal of Engineering Research and Development)
In Floating, Production, Storage, and Offloading (FPSO) vessels, the steel pipes used for water treatment plants are susceptible to corrosion from dissolved oxygen and bacteria in seawater. Chemicals such as oxygen scavengers and biocides are used to combat this. However, using oxygen scavengers can lead to bacterial growth, which can cause a reduction in pipe diameter, increased water pressure, and potential leaks, particularly in the welded sections. Biocides are used to address bacterial growth. In this study, steel coupons were welded with a low-hydrogen electrode, and water from the Lagos lagoon was used to replicate seawater composition. The study employed two different media, agitated and non-agitated, to investigate the effect of water flow dynamics on corrosion rate. Chemical injections did not effectively mitigate corrosion in the tested conditions but sometimes increased it. The results revealed that general corrosion was observed in the samples when no chemical was injected into the system, with an average 0 mm/yr corrosion rate. The agitation of the media led to increased corrosion rates. For biocide injection, the rate increased from 1 mm/y to 2 mm/yr, while in oxygen scavenger solution, the rate increased from an average of 4 mm/yr to 8 mm/yr. Analysis of the cultured seawater parameters showed variations in salinity, total dissolved solids, oxidation-reduction potential, pH, temperature, specific gravity, and conductivity across different media.  The pH of the solution generally increased with time, while the addition of an oxygen scavenger reduced the pH value from approx. 6.5 to 6.2. Agitation of the media and chemical injection increased the conductivity of the solution. Biocide introduction lowered the redox potential, while oxygen scavenger made the redox potential unstable. X-ray diffraction analysis of the steel surface exposed to the seawater indicated the presence of various compounds, suggesting ongoing corrosion processes and the existence of organic and inorganic contaminants. This research has the potential to significantly impact offshore water treatment, providing valuable insights into the challenges and potential solutions for corrosion mitigation in this critical area.